An Analysis of Emergency Drills in Enhancing Self-Readiness and Emergency Preparedness Behavior Among Employees at Taman Dolan Tourist Site - Rachmy Rois; Anita Sulistyorini; Dian Puspitaningtyas Laksana (Medical Technology and Public Health Journal, 2026)
Natural tourism areas are highly vulnerable to disasters, making employees a crucial factor in ensuring visitor safety. One important mitigation strategy is the implementation of emergency drills, also known as emergency response exercises. However, the effectiveness of training in improving employee preparedness remains uncertain. This study aimed to analyzed the effect of emergency drills on self-readiness and emergency preparedness behavior among employees at Taman Dolan Nature Tourism, Batu City. A quantitative approach was used with a pretest-posttest design and Wilcoxon test analysis involving 14 respondents. The intervention consisted of theoretical education and practical simulations on Basic Life Support (CPR) and open wound management. The results showed an increase in the mean self-readiness knowledge score, but it was not statistically significant (p = 0.391). In contrast, emergency preparedness behavior showed a significant increase (p = 0.018), indicating that practical training was more effective in shaping behavioral responses than theoretical material alone. The insignificant change in knowledge may have been influenced by participants’ already high baseline knowledge, the short duration of training, and the limited sample size. This study concludes that emergency drills play an important role in shaping behavioral preparedness. For more optimal outcomes, training should be conducted continuously, tailored to the local context, and accompanied by long-term evaluation. Keywords: Emergency Drills, Emergency Preparedness, Self Readiness, Taman Dolan